Never let go [videorecording (Blu-Ray + DVD)] - Coughlin, KC; Grassby, Ryan; Berry, Halle; Daggs, Percy; Jenkins, Anthony B.; Anderson, Matthew Kevin (Lionsgate, 2024)
"As an evil takes over the world beyond their front doorstep, the only protection for a mother and her twin sons is their house and their family's protective bond. Needing to stay connected at all times even tethering themselves with ropes, they cling to one another, urging each other to never let go. But when one of the boys questions if the evil is real, the ties that bind them together are severed, triggering a terrifying fight for survival"--Container.